Doing more does not mean doing better: the FADOI contribution to the Slow Medicine program for a sustainable and wise healthcare system - Luigi Lusiani; Roberto Frediani; Roberto Nardi; Andrea Fontanella; Mauro Campanini (Italian Journal of Medicine, 2015)
Consistently with its own vision on the necessity to implement a sustainable and frugal medicine, in 2013 the Italian Federation of Associations of Hospital Doctors in Internal Medicine (FADOI) decided to adhere to the Slow Medicine program entitled Doing more does not mean doing better, launched in Italy in late 2012, following the Choosing Wisely® campaign of the American Board of Internal Medicine (ABIM) Foundation started in the USA in 2010. According to the program, FADOI has now produced a list of ten evidence-based recommendations of the do not type, regarding different practices whose benefits for the patients are questionable at least, if not harmful at worst. The list was obtained from a questionnaire submitted to 1175 FADOI members, containing a purposely selected choice of 32 pertinent recommendations already published by Choosing Wisely®, and reflects the qualified opinion of a large number of Italian internists. These recommendations are now endorsed by the FADOI, as a contribution to the discussion among doctors, health professionals, nurses, patients and citizens about what is worth choosing in medicine; they are also meant to promote a shared decision making process in the clinical practice.